Вдосконалення фітокарантинного контролю з позицій фітозабруднення довкілля - Протопопова, В.В.; Шевера, М.В. (Промышленная ботаника, 2004)
New approaches to plant quarantine which take into account the role of phytoquarantine object not only in agrosystems but also as a phytopollutant in natural habitats are proposed. We suggest typifying of the centres or zones of species distribution on zonal-coenotic basis in all types of biotopes; characterization of area differentiation for each species according to the level of its dispersal and injuriousness using annual mapping of the species range for ascertaining rates and direction of distribution; implementation of studying phytoqurantine species on populational basis etc.